How Does Social Capital Offering Economic Development Based on Pesantren Business Units? - Setiawan bin Lahuri; Perdi Pauji; Ainun Amalia Zuhroh (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Human and Social capitals are the main keys to encourage quality economicgrowth. The main role of social capital is to increase business competitiveness ina sustainable manner. The social capital is needed to encourage quality economicgrowth and sustainable competitiveness. Pondok Pesantren is required to supportthe sustainability of pesantren. However, most Pondok Pesantrens have not maximised their economic potential due to the classical understanding that only physical capital is needed for economics. One of the Pondok Pesantren that optimize social capital as an economic instrument is Ponpes Sunan Drajat. So,it is interesting to study the role of social capital in the economic development through pesantren business units. This research is qualitative approach. Primary data collected with Information from PPSD. Secondary data include journal and media sosial. The three main data collection techniques used by observation, interviews and documentation. Observations are carried out as by economic efforts in Islamic Boarding School that involve the community that happen directly. The results showed that the role of Pesantren trust in developing business units is by attractingbusinessunit community, and strengthen the networkties. Value elements play arolein fostering trust, and norms in keeping values intact. Trust intangible valueshavebecome the norm, able to shape the human resources of business unit tobecomea credible, trustworthy, responsible, honest and fair person so the businessunitcan be maximised. This finding strengthens the previous studies that theory ofsocialcapital can play a role in developing the economy.